Shahenshah Net - Mumbai Archive Project Team (Jio Institute, 2024)
Appropriately titled shahenshah, this net is regarded as the king of nets. It has three levels that ensnare fish of various sizes. Only a few people have the ability to craft this complex net, which takes a full day to fix and repair.